Fundamentals of criminal investigation - O'Hara, Charles E. (C.C. Thomas, 2003)
The purpose of this book is to bring the reader to an intermediate level of attainment in the main branches of investigation. From this point he may be able to proceed, with the help of other literature and his experience, to specialized fields of crime detection or non-criminal inquiry. It is the object of the book to introduce the student to investigative work in such a way that he shall, on the one hand, learn what is meant by a complete investigation and acquaint himself with the proofs of the most important crimes, and, on the other, become familiar with the employment of technical method.